CFTR gene analysis in Latin American CF patients: heterogeneous origin and distribution of mutations across the continent - Pérez, Martín M. (2007)
Fil: Pérez, Martín M. ANLIS Dr.C.G.Malbrán. Centro Nacional de Genética Médica; Argentina.